STUDENTS’ PERCEPTIONS OF SYNCHRONOUS SESSIONS WITHIN ONLINE COURSES IN HIGHER EDUCATION - Lamb, Jodi A. (Advances in Social Sciences Research Journal, 2018)
The number of students taking online courses has increased significantly. Helping students be successful in this format is very important. Previous studies have attempted to identify the difficulties that have hindered student academic progress the online environment. Adding a synchronous component to an online course is one method that has been discussed as a way to help students be more successful in online courses. This study sought to answer two research questions: 1. How important do students feel synchronous sessions are to their mastery of online content? and 2. What activities within the synchronous sessions do students feel are the most beneficial? Through email, 200 graduate students in 6 different education programs from a Catholic, Liberal Arts University were invited to participate in an online survey. Participants were asked to rate the importance of online synchronous sessions and their various possible characteristics. Results indicated graduate students found the synchronous online sessions are an important addition to the online course. They also indicated that the content of the sessions was the most important consideration. When structuring synchronous sessions, the participants indicated that instructors should focus on explaining assignments, simplifying content, adding additional content, and supporting group work.